ANALISIS FIQH SIYASAH TENTANG KHILAFAH DALAM KITAB AL-AHKAM AS-SHULTHANIYYAH - David Hanif (Universitas Islam Indonesia, 2022)
This study aims to determine the concept of Khilafah according to Al-Mawardi and Fiqh Siyasah's view of the concept of Khilafah proposed by Al-Mawardi. This research is a normative legal research that uses a historical approach. The results of the study conclude that according to Al-Mawardi, the Imamate or Khilafah system is ideal for administering a country and an imam or Caliph can take on the role of the Prophet's successor in leading the country, guarding religion and governing the world. Al-Mawardi provides a solution for the government system and attempts to create a more democratic political atmosphere by creating a procedure for the appointment of the head of state, namely first, by being elected by Ahlul-Halli Wal-Aqdi, second by granting a mandate from the previous head of state. Fiqh Siyasah's view regarding the idea of Al-Mawardi state administration now used by modern society is the idea of a social contract, namely the relationship between Ahlul-Halli Wal-Aqdi, Wazir and Khailfah or the head of state is a relationship between two parties participating in a social contract or agreement on a voluntary basis, a contract or agreement that gives birth to obligations and rights for both parties on a reciprocal basis.Key Words: Al-ahkam as-shulthaniyah; al-mawardi; fiqh siyasah; caliphateAbstrakPenelitian ini bertujuan untuk mengetahui konsep Khilafah menurut Al-Mawardi dan pandangan Fiqh Siyasah terhadap konsep Khilafah yang dikemukakan oleh Al-Mawardi. Penelitian ini adalah penelitian hukum normatif yang menggunakan pendekatan historis. Hasil penelitian menyimpulkan bahwa menurut Al-Mawardi, sistem Imamah atau Khilafah itu oyeksikan untuk menyelenggarakan sebuah negara dan seorang imam atau Khalifah dapat mengambil peran sebagai pengganti Nabi dalam memimpin negara, menjaga agama dan mengatur dunia. Al-Mawardi memberikan solusi untuk sistem pemerintahan dan upaya menciptakan nuansa politik yang lebih demokratis dengan menciptakan cara tentang prosedur pengangkatan kepala negara, yaitu pertama, dengan cara dipilih oleh Ahlul-Halli Wal-Aqdi, kedua dengan pemberian mandat dari kepala negara terdahulu. Pandangan Fiqh Siyasah terkait gagasan ketatanegaraan Al-Mawardi sekarang dipakai oleh masyarakat modern adalah ide tentang kontrak social, yakni hubungan antara Ahlul-Halli Wal-Aqdi, Wazir dan Khailfah atau kepala negara itu merupakan hubungan antara dua pihak peserta kontrak sosial atau perjanjian atas dasar sukarela, satu kontrak atau persetujuan yang melahirkan kewajiban dan hak bagi kedua belah pihak atas dasar timbal balik.Kata-kata Kunci: Al-Ahkam as-shulthaniyah; al-mawardi; fiqh siyasah; khilafah